A Study on Teaching Vocabulary by Using Flashcards at The Fourth Grade of SDN Panglegur II Pamekasan - Muflihatun Haqiqiyah (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract This paper explores the Way how to teach vocabularies to young learners by using flashcards. This aim at assisting students’ capabilities in studying English vocabularies to introduce new vocabularies since they are still child. Teachers are expected to be the first guidance for directing student being more valiant, more desirable and more active in conveying ideas and communicate with others. This research is focused on three problems. They are 1) How the teacher implement flashcards in teaching vocabularies 2) What are the problems1r that faced by the teacher on teaching vocabularies by using flashcards at the fourth grade of SDN Panglegur II Pamekasan and 3) How to solve the teachers problem on teaching vocabularies. The approach of this research was qualitative data which is gotten by interview, observation and documentation. The result of the research showed that the English teacher found some problems in teaching vocabularies such as difficult took attendance for the students, difficult to make the students active in the class and explained and the students problems was the students confused in differ picture and the solution was the teacher should master the condition and the situation from the class, made creative in every activities, using media and explained the material clearly. Keywords: Study, Teaching. Vocabulary, Flashcards